2012
DOI: 10.1002/adfm.201200595
|View full text |Cite
|
Sign up to set email alerts
|

Following Chemical Charge Trapping in Pentacene Thin Films by Selective Impurity Doping and Wavelength‐Resolved Electric Force Microscopy

Abstract: Charge trapping is one of several factors that limit the performance of organic electronic materials, yet even in pentacene, a prototypical small‐molecule semiconductor, the precise chemical nature of charge trapping remains poorly understood. Here the effects of three chemical trap‐precursor candidates are examined by layering thin‐film pentacene transistors with different pentacene defect species. The resulting charge trapping is studied in each device via scanning‐probe electric force microscopy coupled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Such reactions were not restricted to grain boundaries, and the traps could be cleared by illumination at wavelengths within the absorption spectrum of the film. 793 In contrast, in TES-ADT TFTs, traps were associated with grain boundaries, a similar finding to those in thin Pn films studied by KPFM. 780,794 Ginger and co-workers demonstrated feedback-based timeresolved EFM operation with a 100-μs time resolution, 782 which enabled time-resolved measurements of accumulation of photogenerated charges in OPVs.…”
Section: Microscopic Scalessupporting
confidence: 62%
See 1 more Smart Citation
“…Such reactions were not restricted to grain boundaries, and the traps could be cleared by illumination at wavelengths within the absorption spectrum of the film. 793 In contrast, in TES-ADT TFTs, traps were associated with grain boundaries, a similar finding to those in thin Pn films studied by KPFM. 780,794 Ginger and co-workers demonstrated feedback-based timeresolved EFM operation with a 100-μs time resolution, 782 which enabled time-resolved measurements of accumulation of photogenerated charges in OPVs.…”
Section: Microscopic Scalessupporting
confidence: 62%
“…The experiments revealed that traps in Pn and TIPS-Pn films were carrier concentration-dependent, and were created slowly by reactions of holes with a localized structural defect or impurity. Such reactions were not restricted to grain boundaries, and the traps could be cleared by illumination at wavelengths within the absorption spectrum of the film . In contrast, in TES-ADT TFTs, traps were associated with grain boundaries, a similar finding to those in thin Pn films studied by KPFM. , …”
Section: Experimental Methods For Probing Exciton and Charge Carrier ...mentioning
confidence: 99%
“…These results illustrate that the materials with built-in electric fields can generate spontaneous polarization that works as a driving force to direct the separation of photogenerated electrons and holes and highly reduces the charge recombination. Due to the screening effects, the photogenerated electrons will move along to the polarization direction and lead to the reduction product formation, while the photogenerated holes will move opposite to the polarization direction and lead to the oxidation product formation; during this process, the electron–hole pairs can be highly separated. Furthermore, Dai et al also reported that the built-in electric field combined with the electron effective mass and their synergistic effect on the charge separation and transport in such materials are responsible for the high photocatalytic efficiency . Therefore, it can be seen that photogenerated e–h pairs with high separation efficiency have an effect on the transfer of the charges from the bulk to the surface active site, which is a critical process for a photocatalytic reaction, and thus takes on a significant role for the photocatalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…The latter may trap charge carriers, thus limiting carrier mobility in electronic transistors, or acting as recombination centers in solar cells. These effects seem to be ubiquitous and have been detailed through experimental and theoretical studies on several different organic semiconductors, including acenes, [4][5][6][7][8][9] fullerenes, [10][11][12][13][14] and carbon-based nano-materials. [15][16][17] Metal phthalocyanines (MPcs) belong to a special class of organic materials.…”
Section: Introductionmentioning
confidence: 99%